Pregnancy outcomes of mothers with immune thrombocytopenia - Karanth, Shashikala; Vijay, Christy; Harita, Chaitanya; Mol, Jaya S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: It has been proposed that, thrombocytopenia is the most common haematological abnormality in pregnancy after anaemia. The incidence of severe immune thrombocytopenia (ITP) in pregnancy has been difficult to report because of the rarity of the disease. Objectives were to determine the prevalence, pregnancy outcomes, treatment modalities of ITP mothers over five years in a tertiary health care hospital in South India. Methods: Our study was a retrospective record study, which looked into various aspects of obstetrical outcomes and complications in ITP mothers. Records of the in-patient medical record department (MRD) folders of patients with ITP who delivered at St. Johns Medical Hospital, Bangalore were studied. Results: We identified 53 patients with ITP with a mean age of 25.6+4.6 years, age of diagnosis of ITP at 21.1+5.9 years and gestational age of 36.2+3 weeks. In our study 17 (32%) were acute and 36 (67.1%) were chronic ITP. In our study 39.6% had history of at least one prior pregnancy loss. Patients with ITP at 35-37 weeks were induced with PGE1 (35.7%) in comparison to those with PGE2 (p≤0.001). Post-partum haemorrage (PPH) was seen in 7.5% of the pregnancies and all four were mothers with chronic ITP. Severe preeclampsia in ITP mothers was seen in 2 (66.7%). Conclusions: Chronic ITP in pregnancy poses more risks to mother and foetus as seen with the higher chance of PPH etc. Mothers with ITP should be screened antenatally as the chances of anomalies are high in the foetus.